Sonographic abnormalities in pregnancies conceived following IVF with and without preimplantation genetic testing for aneuploidy (PGT-A) - Riestenberg, Carrie K. (J Assist Reprod Genet, 2021)
PURPOSE: To report the rate of fetal anomalies detected on anatomy ultrasound in pregnant patients who underwent IVF with preimplantation genetic testing for aneuploidy (PGT-A) compared to patients who conceived following IVF with unscreened embryos and age-matched patients with natural conceptions. METHODS: Retrospective cohort study at a single maternal-fetal medicine practice. Patients with singleton pregnancies who had a mid-trimester anatomy ultrasound between January 2017 and December 2018 were screened for inclusion. A total of 712 patients who conceived after IVF with or without PGT-A were age-matched with natural conception controls. The primary outcome was the rate of fetal and placental anomalies detected on mid-trimester anatomical survey. Secondary outcomes included the rates of abnormal nuchal translucency (NT), second trimester serum analytes, non-invasive prenatal testing (NIPT), and invasive diagnostic testing. RESULT(S): There were no differences in the rate of fetal anomalies in patients who underwent IVF with PGT-A compared to patients who conceived following IVF with unscreened embryos and age-matched patients with natural conceptions. Rate of abnormal NT, high-risk NIPT, and abnormal invasive diagnostic testing were also similar. Patients who conceived after IVF with or without PGT-A had higher rates of abnormal placental ultrasound findings and abnormal second trimester serum analytes compared to natural conception controls. CONCLUSION: The use of PGT-A was not associated with a difference in risk of fetal anomaly detection on a mid-trimester anatomical survey. The results of this study highlight the importance of improved patient counseling regarding the limitations of PGT-A, and of providing standard prenatal care for pregnancies conceived through ART, regardless of whether PGT-A was performed. SUPPLEMENTARY INFORMATION: The online version contains supplementary material available at 10.1007/s10815-021-02069-5.